Torque behaviour during cycling sprints from different pedalling frequencies - Imbery, F.; Leo, P.; Wakefield, J.; Schoberer, U. (Journal of Science and Cycling, 2022)
Professional road cycling events often result in a bunch sprint at the end of a race, where power outputs of >1.200 W have been recorded. To hit those power outputs high torque and cadence is needed. The purpose of this study was to investigate torque and cadence relationship in cycling sprints in field condition. Five athletes (mean±SD; female: N=3, 23±2 years, 172±cm, 59±3 kg, male: N=2, 27±3.5 years, 179±9 cm, 79±6 kg) executed five maximum sprints over 6-10 s starting from different cadences. Using the latest generation of crank based cycling power meters (SRM Powermeter 9, Jülich, Germany) and data of torque, power, angular velocity, and angle were recorded every 5 ms. Maximum Torque demonstrated a large effect (d=1.4 to 4.0) across all cadence ranges (delta: 25 to 72 Nm). However, maximum on power demonstrated a small to large effect (d=.3 to 1.1). Sex differences demonstrated a large effect for peak Torque, maximum on power, and maximum one second power, (d=2.3 to 3.2) and small effects for Angleft and Angright (d=.2 to .3). The findings suggest a deeper analysis and understanding of cycling sprints in field. Furthermore, cycling sprints are very different comparing sexes.